Narrow band imaging as a noninvasive tool for evaluation of the severity of inflammation in patients with ulcerative colitis in Kafr-El-Sheikh university, Egypt - Aya Mohammed Mahros; Eman Mohammad Saied; Abdel Atty Ibrahem Abdelatty; Mohammed Khorshid; Hassan Elsayed El batea (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the effectiveness of narrow-band imaging in determining the severity of inflammation in ulcerative colitis patients in relation to histological activity. Method: The cross-sectional study was conducted at Kafrelsheikh University Hospital, Egypt, from June 2021 to May 2022, and comprised patients regardless of age and gender who had ulcerative colitis and visited the endoscopy unit. After taking detailed history, the patients were subjected to physical examination and laboratory tests which included complete blood count, international normalised ratio, erythrocyte sedimentation rate and faecal calprotectin. Colonoscopy with narrow-band imaging, biopsy and histopathological assessment were done as part of clinical evaluation. Data was analysed using SPSS 20. Result: Of the 100 patients, 55(55%) were male and 45(45%) were females. The overall mean age was 33.72±10.29 years (range: 11-56 years). There were 73(73%) patients who were married, 12(12%) had positive family history and 19(19%) were smokers. Besides, 18(18%) patients received biological therapy. There was significant positive correlation between histopathological and endoscopic scores (p<0.05). Also, there was a significant positive correlation between histopathological score and findings of narrow-band imaging (p<0.05). There were 10(10%) patients who were found to have dysplasia that was not diagnosed with colonoscopy. Conclusion: Narrow-band imaging was found to have a significant correlation with the histologically determined degree of inflammation. Keywords: Narrow-band imaging, Ulcerative colitis, Histological scoring, Smokers, Leukocyte L1 antigen complex, Colonoscopy, Biopsy, Inflammation, Biological therapy.